A Comparative Analysis of Immunohistochemical Profile of Primary and Metastatic Endometrial Endometrioid Carcinoma. (28th October 2020) - Xu, K; Ye, Q; Han, L; Zhong, M
Abstract: Introduction/Objective: Beta catenin plays an important role in cancer tumorigenesis and have been found to be associated with metastasis in a variety of tumors. Analyzing TCGA data, we found that 30% of endometrial endometrioid carcinoma cases have beta-catenin mutations. We hypothesize that beta-catenin mutation may be associated with metastasis of endometrial endometrioid carcinoma. ER and PR expression was also compared to determine any changes after metastasis. Methods: Retrospective institutional review of all endometrial endometrioid carcinoma (192 cases) between 2011 to 2018 was performed, including 149 cases of FIGO grade I, 38 cases of FIGO grade II and 5 cases of FIGO grade III. 19 cases with paired primary and metastatic specimen were identified. Immunohistochemistry staining (IHC) was carried out for ER, PR and beta-catenin. Results: Median patient age was 56 years. The most common metastatic site was vagina, accounting for 68% of metastasis (14/19), followed by bladder (3/19), lung (2/19) and rectum (1/19). The primary and metastatic carcinoma of all 19 cases exhibit very similar morphology. All of those cases were positive and concordant for ER and PR in primary and metastatic endometrioid carcinoma. On the other hand, nuclear beta-catenin staining caused by mutation was positive in 5 metastatic carcinoma but not in primary carcinoma. Conclusion: IHC expression of ER and PR remains unchanged between primary and metastatic carcinoma, demonstrating the reliability of ER and PR to confirm the origin of metastatic carcinoma. 26% of the metastatic carcinoma (5/19) exhibit nuclear beta-catenin staining but not in primary carcinoma, suggesting the possible role of beta-catenin in metastasis of endometrial endometrioid carcinoma.